Fair trade : - DeCarlo., Jacqueline (Oneworld, 2007)
Jacqueline DeCarlo reveals why the movement has come to mean far more than just bananas, coffee, and chocolate. Grounded in the inspiring power of Fair Trade as a positive alternative to poverty, environmental destruction, and human exploitation, this enlightening book explains how we can make a difference. Providing an accessible explanation of the principles behind the movement and tracing its development into the powerful economic and social justice tool it is today, Fair Trade: A Beginner’s Guide will rouse readers of all backgrounds to help end global injustice. Jacqueline DeCarlo is Fair Trade Program Officer of Catholic Relief Services.